History and Development of the Problem Play in English Literature - Priydarshi, Ashok Kumar (Journal of Advanced Research in English & Education; Vol 6 No 3 (2021): Journal of Advanced Research in English and Education, 2021)
The genre, ‘problem play’ originated in France in the late 19th century. Notable example are Ibsen’s ‘A Dolls’ House’ (1879), questioning the subordination of women in marriage, Shaw’s ‘Mrs Warren’s Profession’ (1902), examining attitudes towards prostitution; and Galsworthy’s ‘Justice’ (1910), exposing the cruelties of solitary confinement and the legal system. Some plays by later writers such as A. Wesker, J. McGrath, Caryl Churchill, H. Brenton and D. Hare also raise contemporary issues, often using a wider canvas than their predecessors. How to cite this article: Priydarshi AK. History and Development of the Problem Play in English Literature. J Adv Res Eng & Edu 2021; 6(3): 1-2. DOI: https://doi.org/10.24321/2456.4370.202104